Sinusoidal frequency doubler and full-wave rectifier using translinear current conveyor - Surakampontorn, W.; Anuntahirunrat, K.; Riewruja, V. (My University, 1998)
A simple circuit design technique for realising both a sinusoidal frequency doubler and a full-wave rectifier, employing a translinear current conveyor and current mirrors as active circuit elements, is proposed. The implementation method uses the inherited translinear loop of the translinear current conveyor to perform frequency doubling and rectification. The performance of the scheme is demonstrated by PSPICE simulations.